2022
DOI: 10.3390/ijms23073698
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Gut Microbiota and Endothelial Dysfunction in the Development of Arterial Hypertension in Animal Models and in Humans

Abstract: The maintenance of the physiological values of blood pressure is closely related to unchangeable factors (genetic predisposition or pathological alterations) but also to modifiable factors (dietary fat and salt, sedentary lifestyle, overweight, inappropriate combinations of drugs, alcohol abuse, smoking and use of psychogenic substances). Hypertension is usually characterized by the presence of a chronic increase in systemic blood pressure above the threshold value and is an important risk factor for cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 252 publications
(242 reference statements)
0
16
0
Order By: Relevance
“…Previous examination of the mdx muscle microvasculature showed defective endothelial layer and reduced vessels (Bella et al , 2020). Accumulating evidence has shown that gut microbiome can influence the balance of vascular homeostasis (Kiouptsi & Reinhardt, 2018; Battson et al , 2019; Brunt et al , 2019; Maiuolo et al , 2022). Staining of whole TA muscle sections of ABX‐mdx FMT_C57Bl mice demonstrated that eubiotic FMT efficiently increased the number of CD31 + capillaries and small arterioles expressing α‐smooth muscle actin (αSMA) (Fig 7L and M).…”
Section: Resultsmentioning
confidence: 99%
“…Previous examination of the mdx muscle microvasculature showed defective endothelial layer and reduced vessels (Bella et al , 2020). Accumulating evidence has shown that gut microbiome can influence the balance of vascular homeostasis (Kiouptsi & Reinhardt, 2018; Battson et al , 2019; Brunt et al , 2019; Maiuolo et al , 2022). Staining of whole TA muscle sections of ABX‐mdx FMT_C57Bl mice demonstrated that eubiotic FMT efficiently increased the number of CD31 + capillaries and small arterioles expressing α‐smooth muscle actin (αSMA) (Fig 7L and M).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher adherence to MedDiet has been associated with higher biodiversity of microbiota, which in turn seems to be associated with a regulation of cognitive functions [ 70 ]. In addition, a state of eubiosis has been shown to help reduce endothelial dysfunction, which is another known risk factor of cognitive [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unique composition of gut microbiota in each sample can be influenced by various things, such as food, intestinal mucosa, drug consumption/abuse, the immune system, and the microbiota itself (Maiuolo et al 2022). Yokoyama et al (2020) have report that blood pressure will be lower in those who consume vegetarian foods than omnivorous foods.…”
Section: Discussionmentioning
confidence: 99%